Analysis of the Effect of Work Stress and Work Motivation on Lecturer Teaching Performance: Case Study at Mandiri Bina Prestasi Polytechnic - Mardaus Purba; Lennaria L. Tarigan; Erni Dewi Munthe; Veronika Saragih; Mery Sulianty H. Sitanggang (Enrichment : Journal of Management, 2022)
Mandiri Bina Prestasi Polytechnic at its inception in 2004 had its own charm, but since 2012 it has experienced a decline in public interest and trust and continues to decline until now. Internal problems are clearly visible, including low teaching performance both in the process of planning, implementing and evaluating learning. Lecturers seem to lack encouragement to carry out the learning process properly and there are symptoms of stress experienced by lecturers related to their work. Scientific studies are needed on the effect of work stress and work motivation on the teaching performance of lecturers at the Bina Prestasi Mandiri Polytechnic to be able to provide a solution for handling it using the approach used based on McClelland's theory. This study uses multiple linear regression to determine the effect of work stress (physiological, psychological, behavioral, work conflict, task characteristics, and influence of leadership), and work motivation (wages/salary, desire to progress, and need for affiliation). on the teaching performance of lecturers at the Mandiri Achievement Development Polytechnic. The subjects in this study were all permanent lecturers at the Bina Prestasi Polytechnic, totaling 48 people. This study proves that the teaching performance of lecturers at the Mandiri Bina Prestasi Polytechnic can be significantly influenced by work stress and work motivation at a significant level of 5%. Partially it was also found that work stress and work motivation each had a significant effect on the performance of the Bina Prestasi Mandiri Polytechnic lecturers, where work stress had an effect on work motivation. The variables of work stress and work motivation can explain 43.70% of their influence on the teaching performance variables of lecturers at the Bina Prestasi Mandiri Polytechnic while the remaining 56.3% is the influence of other independent variables not examined in this study.